(untitled) (Bangladesh Journal of Animal Science, 2021)
The present study was aimed to determine growth and blood parameters of soybean based milk replacer fed kids and naturally suckled counterparts in three villages of Mymensingh Sadar, Bangladesh. Twelve Black Bengal kids were allocated into two treatment groups; one group (n=6) was reared with milk replacer while the other (as control; n=6) was reared naturally keeping with their dam. Live weight and body measurement of kids were recorded weekly. Blood samples were collected from 8 weeks old kids to determine their red blood cell (RBC), white blood cell (WBC), haemoglobin (Hb), packed cell volume (PCV) and differential leukocyte count (DLC). The average initial live weight of the suckled and replacer fed kids did not show significant difference (p<0.05). The average final live weight was significantly (p<0.05) higher in artificially fed males (7.7±0.18 kg) than naturally suckled male (6.89±0.24 kg) kids. Body length, wither height and heart girth were significantly (p<0.05) higher in milk replacer fed male kids than naturally suckled counterparts. RBC count was significantly (p<0.05) higher in artificially fed group than naturally suckled kids. Hb, PCV and DLC did not differ significantly (p>0.05) between treatment groups. In conclusion, feeding with soybean based milk replacer enhanced growth of kids comparing naturally reared counterparts. Bang. J. Anim. Sci. 2021. 50 (1):22-27